Characterization of circular RNA profiles of oviduct reveal the potential mechanism in prolificacy trait of goat in the estrus cycle - Sun, Zhipeng; Hong, Qionghua; Liu, Yufang; He, Xiaoyun; Di, Ran; Wang, Xiangyu; Ren, Chunhuan; Zhang, Zijun; Chu, Mingxing (Frontiers in Physiology, 2022)
The mammalian oviduct is functionally highly diverse during the estrus cycle. It provides a suitable milieu for oocyte maturation, sperm capacitation, fertilization, early embryo development and transportation. While there have been many studies of molecular mechanisms on the kidding number of goats, a systematic analysis by which the underlying circular RNAs (circRNAs) changes in the oviduct related to prolificacy traits is lacking. Herein, we present a comprehensive circRNA atlas of the oviduct among high- and low-fecundity goats in the follicular phase (FH vs. FL), luteal phase (LH vs. LL), and estrus cycle (FH vs. LH; FL vs. LL) to unravel their potential regulatory mechanisms in improving kidding number. We generated RNA sequencing data, and identified 4,078 circRNAs from twenty sampled Yunshang black goats. Many of these circRNAs are exon-derived and differentially expressed between each comparison group. Subsequently, eight differentially expressed (DE) circRNAs were validated by RT‒qPCR, which was consistent with the RNA-seq data. GO and KEGG enrichment analyses suggested that numerous host genes of DE circRNAs were involved in the hormone secretion, gamete production, fertilization, and embryo development processes. The competing endogenous RNA (ceRNA) interaction network analysis revealed that 2,673 circRNA–miRNA–mRNA axes (including 15 DE circRNAs, 14 miRNAs, and 1,699 mRNAs) were formed, and several target genes derived from the ceRNA network were associated with oviduct functions and reproduction, including SMAD1, BMPR1B, IGF1, REV1, and BMP2K. Furthermore, miR-15a-5p, miR-181b-5p, miR-23b-5p, miR-204-3p, and miR-145-5p might play important roles in reproduction. Finally, a novel circRNA, circIQCG, was identified as potentially involved in embryo development. Overall, our study provides a resource of circRNAs to understand the oviductal function and its connection to prolificacy trait of goats in the differentiation estrus cycle.